RingAuth dataset - Sturgess, J (University of Oxford, 2023)
We collected inertial sensor data on a smart ring and a smartwatch, both worn on the same arm, and from a Raspberry Pi IMU mounted on a closed door as users performed activities. The data contains data from users (n=21) as they performed five types of gesture: tap gestures as users performed mobile payments on a number of point-of-sale terminals with (i) the smart ring and (ii) the smartwatch, and knock gestures as users knocked on the door in patterns of (iii) 3 knocks at a time, (iv) 5 knocks at a time, and (v) secret knocks chosen by the user. All of these gestures can be used to authenticate the user.